Toxoplasmosis in Primiparus Pregnant Women and Their Neonates - S Noorbakhsh; S Mamishi; S Rimaz; SHR Monavari (Tehran University of Medical Sciences, 2002)
The prevalence of primary infection with T. gondii in pregnant women and risk of congenital infection in their neonates in various parts of Tehran are unknown. The prevalence rate of antibodies to T. gondii ranges from 24% in Tehran to 62.7% in Babol. This study describes the epidemiology of toxoplasma infection in pregnant women in Tehran and risk factors of congenital toxoplasmosis in newborn among preterm infants and full- term infants born from these mothers. A cross sectional study was carried out in 140 primiparus women living in various part of Tehran. Initially from each case a questionnaire was completed by the authorized physician, followed by clinical exams in newborns. The birth certificate was the data source used for such as gestational age, birthweigt, etc. The centrifuged blood specimens from all pregnant women are screened using an assay for Toxoplasma- specific IgM and IgG based on preliminary evidence in Iran. Specific toxo- IgM was positive in 7.1% (90% of them were also IgG positive) , toxo – IgG was positive in 34.3% of mothers. Mean age of IgG positive mothers (22.49±4.22), mean age of IgM positive mothers (19.90± 3.48). There were significantly differences between living place of mothers and IgG positive (p=0.007) . There were significantly differences between living place of mothers (East and central) and IgM positive (Fisher test = 0.023). Elaborating an epidemiological profile and risk correlates might help focus prenatal education and newborn screening strategies. Prenatal screening could be more easily justified in central part of Tehran because low incidence populations detected and probably treatment of mothers infected during pregnancy led to lower rates of transmission to the newborn. In contrast, in eastern part of Tehran due to high seroprevalence rate detected, newborn screening is relatively inexpensive and efficient.